Mechanisms for Concluding Oil Contracts in the Kurdistan Region Government (KRG) under the International Law and Iraqi Legal System - AMIN, REBWAR MOHAMMED MOHAMMED (The journal of contemporary issues in business and government, 2021)
The adoption of the new Iraqi constitution, a federal, republican, representative, and democratic system had an impact on the distribution of competencies and powers between the center and the regions. What concerns us here is an issue, who is the authority authorized to conclude contracts related to oil wealth in accordance with this constitution? The new constitution has dealt with the exploitation of oil wealth as the most important natural wealth of the country - explicitly through articles (111) and (112), and Article (112) stipulates that the exploitation of this wealth is through the issuance of a law that regulates the mechanism of exploitation. So far to regulate the provisions of exploitation of this wealth - because of differences between the political blocs on it. Ratification of the majority of the rights of the people of Kurdistan from the permanent constitution of 2005, including the rights of people to the natural resources, especially oil and gas, in two articles (111,112), but until now it will not settle this problem to determine the stake of the Kurdish people and the existence of a continuing conflict between the Kurdistan Region and the center in how to manage oil and gas. This research investigates the legitimacy and authority of the Kurdistan Regional Government and its people to invest and conclude oil and gas contracts in accordance with the constitutional framework, laws, decisions, international, Iraqi and Kurdish agreements and treaties to solve this problem.